Public Health and Bioethics, Reflections on Sars-Cov-2 (Covid-19) in Colombia - Vélez Álvarez, Consuelo; Betancurth Loaiza, Diana Paola; Holguín Zuluaga , Juan Alejandro (Revista Cuidarte, 2020)
The quick spread of the COVID-19 disease has generated the establishment of coordination mechanisms, control and lengthy actions by actors and/or agents, which has triggered border barriers between communities and people to curb the contagion. This situation has also produced fear of infection and a survival instinct that has inevitably altered the perception of the other, which is viewed with mistrust when configuring itself as a potentially infectious person; in extreme cases there is even discrimination or exclusion.However, this should not affect collaboration to fight at all levels: governments, public and private sectors, civil society, international and regional organizations, while overcoming selfishness and segregation. So much so that the ethical ideal must transcend political borders, geographical limits and cultural differences, so that the focus is on the common needs of people and the joint responsibility to dialogue about concrete solutions to overcome the difficult situation. In other words, there is a need for constructive cross-disciplinary meetings between governmental and scientific actors that help overcome the crisis.How to cite this article: Vélez-Álvarez Consuelo, Betancurth Loaiza Diana Paola, Holguín Zuluaga Juan Alejandro.  Public Health and Bioethics, Reflections on Sars-Cov-2 (Covid-19) in Colombia. Revista Cuidarte. 2021;12(1):e1369. http://dx.doi.org/10.15649/cuidarte.1369
Keywords: Bioética; Salud Pública; Infeccinfecciones por Coronavirus; Pandemias; Regulación Gubernamental